2018
DOI: 10.1007/s00018-018-2795-y
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the molecular and biological functions of the oxysterol-binding protein family

Abstract: Oxysterol-binding protein (OSBP) and OSBP-related proteins (ORPs) constitute a large eukaryotic gene family that transports and regulates the metabolism of sterols and phospholipids. The original classification of the family based on oxysterol-binding activity belies the complex dual lipid-binding specificity of the conserved OSBP homology domain (OHD). Additional protein- and membrane-interacting modules mediate the targeting of select OSBP/ORPs to membrane contact sites between organelles, thus positioning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
97
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 159 publications
0
97
0
Order By: Relevance
“…In 2010, Shair et al reported that OSBP and ORP4 L, two members of the oxysterol binding protein (ORP) superfamily implicated in lipid/sterol transport and sensing are the major protein targets of OSW-1. [4,5] Using competitive binding assays based on recombinant OSBP and ORP4 L and [ 3 H]-25-HC, their endogenous ligand, OSW-1 exhibits high affinity toward these proteins (K i = 26 nM for OSBP and 54 nM for ORP4 L). However, the link between the inhibition of OSBP and ORP4 L and apoptotic induction has remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, Shair et al reported that OSBP and ORP4 L, two members of the oxysterol binding protein (ORP) superfamily implicated in lipid/sterol transport and sensing are the major protein targets of OSW-1. [4,5] Using competitive binding assays based on recombinant OSBP and ORP4 L and [ 3 H]-25-HC, their endogenous ligand, OSW-1 exhibits high affinity toward these proteins (K i = 26 nM for OSBP and 54 nM for ORP4 L). However, the link between the inhibition of OSBP and ORP4 L and apoptotic induction has remained unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the long-term, compound-induced reduction of OSBP in cells presents a new route to broad spectrum anti-Enterovirus activity, including as a novel route to antiviral prophylactic treatment through small molecule targeting a human host protein.O xysterol-binding protein (OSBP) and the OSBP-related proteins (ORPs) are a family of lipid and sterol binding proteins conserved in all eukaryotes. 1,2 The 12 OSBP/ORP human proteins share a conserved ∼50 kDa, C-terminal ligand binding domain. 1,2 OSBP and ORP4, the member most closely related to OSBP, share substantial sequence similarity, and both contain N-terminal pleckstrin homology (PH) and FFAT domains.…”
mentioning
confidence: 99%
“…3−5 The PH and FFAT domains alter OSBP cellular localization upon binding of ligands in the C-terminal ligand binding domain. 1,2 OSBP binding partners, including several regulatory proteins, have been reported. 1,2 OSBP gene expression and protein regulation are not well-defined.…”
mentioning
confidence: 99%
See 2 more Smart Citations